Clonal Hematopoiesis Is Associated With Higher Risk of Stroke. Issue 3 (8th November 2021) - Bhattacharya, Romit; Zekavat, Seyedeh M.; Haessler, Jeffrey; Fornage, Myriam; Raffield, Laura; Uddin, Md Mesbah; Bick, Alexander G.; Niroula, Abhishek; Yu, Bing; Gibson, Christopher; Griffin, Gabriel; Morrison, Alanna C.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Clonal hematopoiesis of indeterminate potential (CHIP) is a novel age-related risk factor for cardiovascular disease–related morbidity and mortality. The association of CHIP with risk of incident ischemic stroke was reported previously in an exploratory analysis including a small number of incident stroke cases without replication and lack of stroke subphenotyping. The purpose of this study was to discover whether CHIP is a risk factor for ischemic or hemorrhagic stroke. Methods: We utilized plasma genome sequence data of blood DNA to identify CHIP in 78 752 individuals from 8 prospective cohorts and biobanks. We then assessed the association of CHIP and commonly mutated individual CHIP driver genes ( DNMT3A, TET2, and ASXL1 ) with any stroke, ischemic stroke, and hemorrhagic stroke. Results: CHIP was associated with an increased risk of total stroke (hazard ratio, 1.14 [95% CI, 1.03–1.27]; P =0.01) after adjustment for age, sex, and race. We observed associations with CHIP with risk of hemorrhagic stroke (hazard ratio, 1.24 [95% CI, 1.01–1.51]; P =0.04) and with small vessel ischemic stroke subtypes. In gene-specific association results, TET2 showed the strongest association with total stroke and ischemic stroke, whereas DMNT3A and TET2 were each associated with increased risk of hemorrhagic stroke. Conclusions: CHIP is associated with an increased risk of stroke, particularly with hemorrhagic and small vessel ischemic stroke. Future studies clarifying the relationship between CHIP and subtypes of stroke are needed.